Evaluating the Influence of Passive Design Strategies on Cooling Energy Demand in Local Adobe, Stone and Concrete Dwellings in Wadi Hadramout, Yemen - Al-hebshi, Omar (Transactions on Engineering and Computing Sciences, 2023)
Vernacular architecture is the outcome of hundreds of years of optimization to provide comfortable dwellings and adapt with local climate conditions using available resources and construction techniques. Traditional buildings use passive cooling measures to provide thermal comfort without mechanical systems. In least developed countries like Yemen, severe power deficiency and consequent blackouts limit the use of air conditioning to provide indoor thermal comfort. In Hadramout province east of Yemen, climate responsive adobe dwellings are fading-out gradually and being replaced with modern buildings that neglect local climate and depend entirely on mechanical ventilation to provide comfort specially in summer. This paper investigates energy efficiency and the potential influence of passive design strategies in reducing energy demand for cooling in adobe, concrete and stone local houses in Wadi Hadramout during summer. The results indicated that adobe house requires 51.77% and 51.29% lower energy for cooling compared to concrete and stone houses respectively when refrigerated cooling is used. In case of the evaporative Cooling, adobe house requires 66.03% and 65.82% lower energy compared to concrete and stone houses respectively. Furthermore, the results showed that some passive design strategies have a remarkable impact on improving energy efficiency of the tested houses.